Education under National Socialism: Ideology, Programs and Practice - Jakob Benecke; Jörg-W. Link (Locus, 2022)
The article provides a condensed, introductory overview of National Socialist formation education in the Hitler Youth and school. It is based on the author’s own research and relevant presentations. Education under National Socialism was characterized by the interplay of a racist worldview and the regime’s totalitarian will to rule. For Nazi education, this meant that the political took precedence over all social issues, including all issues relevant from the perspective of educational theory. In our analysis, we distinguish between two levels: the level of standardization and the level of educational practices in the Hitler Youth and school. Particularly during World War II, political demands were increasingly rigidly enforced, and adolescents were increasingly instrumentalized for their purposes. The National Socialists’ aspirations for total control compared to the educational reality exhibited correspondences as well as discrepancies and contradictions. Against the background of traditional tasks of education, the verdict on Nazi education from a normative point of view is clearly negative. However, if one also looks at National Socialist educational practices, one notices numerous characteristic ambivalences – between the partly contradictory demands of the National Socialist regime, but also between its educational practices and its attempts at realization. On the one hand, National Socialists achieved comprehensive formative successes, while on the other hand they often failed because of their totalitarian objectives.